Approximation of bounded holomorphic and harmonic functions by Fejér means - Savchuk, V. V.; Savchuk, M. V.; Chaichenko, S. O. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
We compute the exact values of the exact upper bounds on the classes of bounded holomorphic and harmonic functionsin a unit disk for the remainders in a Voronovskaya-type formula in the case of approximation by Fej´er means. We alsopresent some consequences that are of independent interest.